Current understanding of genetic associations with delayed hypersensitivity reactions induced by antibiotics and anti-osteoporotic drugs - Wung, Chih-Hsuan; Wang, Chuang-Wei; Lai, Kuo-Chu; Chen, Chun-Bing; Chen, Wei-Ti; Hung, Shuen-Iu; Chung, Wen-Hung; , Taiwan Severe Cutaneous Adverse Reaction Consortium (Frontiers in Pharmacology, 2023)
Drug-induced delayed hypersensitivity reactions (DHRs) is still a clinical and healthcare burden in every country. Increasing reports of DHRs have caught our attention to explore the genetic relationship, especially life-threatening severe cutaneous adverse drug reactions (SCARs), including acute generalized exanthematous pustulosis (AGEP), drug reactions with eosinophilia and systemic symptoms (DRESS), Stevens–Johnson syndrome (SJS), and toxic epidermal necrolysis (TEN). In recent years, many studies have investigated the immune mechanism and genetic markers of DHRs. Besides, several studies have stated the associations between antibiotics- as well as anti-osteoporotic drugs (AOD)-induced SCARs and specific human leukocyte antigens (HLA) alleles. Strong associations between drugs and HLA alleles such as co-trimoxazole-induced DRESS and HLA-B*13:01 (Odds ratio (OR) = 45), dapsone-DRESS and HLA-B*13:01 (OR = 122.1), vancomycin-DRESS and HLA-A*32:01 (OR = 403), clindamycin-DHRs and HLA-B*15:27 (OR = 55.6), and strontium ranelate (SR)-SJS/TEN and HLA-A*33:03 (OR = 25.97) are listed. We summarized the immune mechanism of SCARs, update the latest knowledge of pharmacogenomics of antibiotics- and AOD-induced SCARs, and indicate the potential clinical use of these genetic markers for SCARs prevention in this mini review article.